Experimental Study of Water Lens Photovoltaic Concentrating System - Qudsi, Dania (جامعة بوليتكنك فلسطين - طاقة)
New technology of photovoltaic concentrators was employed, water lens that was built from cheap, easily and available materials, water and hyper elastic linear low density polyethylene plastic foil. It was an effective way of improving efficiency by a comparison of experiment with water lens and without lens as a concentrator investigated the thin film solar cell performance. It was found an increasing in output power also the efficiency because it is concentrate the light and increase in the intense light which focused in small area that lead to substitute the large area of solar cell used in traditional way in to smaller effective solar cell. series of experiment was done, it was found distilled water lens (DWL) at thickness 5cm was best lens that effect on the performance of PV cell and gives higher efficiency about 17.08%. ُ
CD , no of pages 76 , 31045 , طاقة 9/2019 , in the store
Keywords: Water Lens Photovoltaic Concentrating